Efficacy and safety of acupuncture with moxibustion for knee osteoarthritis: a meta-analysis of randomized controlled trials - Rui-Xin Zhu; Xing Li; Zhao-Bo Yan; Cheng Chen; Wei Zhai; Heng-Cai Zhang; Wen-Juan Ma; Fu-Kun Wang; Mi Liu; Ge-Shu Du (Systematic Reviews)
Abstract Background Osteoarthritis (OA) is prevalent, yet its management remains challenging. This meta-analysis aims to evaluate the efficacy of acupuncture combined with moxibustion versus other standard treatments in patients with knee osteoarthritis (KOA) based on randomized controlled trials (RCTs). Methods Searches were conducted in Ovid MEDLINE, Embase, and the Cochrane Central Register of Controlled Trials to retrieve relevant RCTs. Data on baseline characteristics, treatment efficacy, and adverse events were extracted. The analysis utilized pooled weighted mean differences (WMD) and risk ratios (RR) with 95% confidence intervals (CIs) to assess the superior treatment modality. Results A total of 18 RCTs were included. Acupuncture combined with moxibustion demonstrated significant improvement in the visual analog scale (VAS) for pain and the long-term (> 60 weeks) Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) scores for pain, stiffness, and physical function compared to other treatments. In contrast, short- (< 4 weeks) and mid-term (6–60 weeks) WOMAC outcomes for pain, stiffness, and physical function indicated varied results. The overall efficacy rate also favored the combined therapy significantly in the short- and mid-term evaluations. Notably, this therapy was associated with fewer adverse events. Conclusion The meta-analysis reveals that acupuncture combined with moxibustion is notably more effective and safer than other treatment modalities for KOA, particularly during mid- and long-term follow-up periods.